Plant Regeneration Efficiency of Two Scented Indica Rice Varieties Pusa Basmati 1 and Kalanamak (Plant Tissue Culture and Biotechnology, 2013)
This study was undertaken to establish a regeneration protocol for two scented indica rice varieties, namely Pusa Basmati1 and Kalanamak. Callus culture in Pusa Basmati1 was initiated in MS containing 2.0 mg/l of 2,4-D. Optimum requirement of growth hormones for callus induction in Kalanamak was 1.5 mg/l of 2,4-D supplemented with 0.1 mg/l each of NAA and BAP in MS. Shoot regeneration in Pusa Basmati1 initiated in MS containing 2.0 mg/l BAP, 0.5 mg/l each of NAA and Kn. There was no shoot initiation in MS with same composition in Kalanamak. The shoot regeneration was successfully initiated and achieved in Dl medium supplemented with 2.0 mg/l BAP, 0.2 mg/l each of IAA, NAA and Kn, 500 mg/l each of proline and glutamine and 800 mg/l casein hydrolysate. The calli derived from mature seed embryo produced fertile green plants. The plants were successfully transferred to field with normal flowering. DOI: http://dx.doi.org/10.3329/ptcb.v22i2.14206 Plant Tissue Cult. & Biotech. 22(2): 163-169, 2012 (December)